Evaluation of Thermal Properties of Water Blends and Nano ALSIC Blends for Heat Transfer Applications - A. Haritha Reddy, Dr. P. Usha Sri (International Journal of Advanced Science and Technology, 2019)
Heat transfer fluids are a crucial parameter that affects the size and costs of heat exchangers. However, the available coolants like water and oils have low thermal conductivities, which put many limitations to the development of heat transfer to achieve high performance cooling. The need for development of new classes of fluids which enhance the heat transfer capabilities attracted the attention of many researchers A “nanofluid” is a fluid with suspended fine nanoparticles which increases the heat transfer properties compared with the original fluid. Nanofluids are considered a new generation of heat transfer fluids and are considered two-phase fluids of liquid solid mixtures. The efficiency of the fluid could be improved by enhancing its thermal properties, especially the thermal conductivity, and it is expected that the nanofluids will have a greater thermal conductivity than the base fluids.